Secure Localization Technology Based on Dynamic Trust Management in Wireless Sensor Networks. Issue 4 (1st July 2021) - Peng, LI; Xiaotian, YU; He, XU; Ruchuan, WANG
Abstract : Wireless sensor networks have critical applications in various fields, and the algorithm of their secure localization has become a vital technology to support a network. In the light of the self‐organization, random deployment and dynamic topology, the localization process is vulnerable to various kinds of malicious attacks. The model of dynamic trust management for a given node is proposed to deal with security concerns in wireless sensor networks. The trust computation is divided into three stages, which are the stage of trust initialization, trust establishment, and trust evolution. The initial value of a global trust relationship is established through a corresponding global trust relation graph in the initial stage of trust. The trust value of each node is calculated by the attribute value in the stage of trust establishment. In the evolution of trust, the iterative process of trust value is accelerated via the finite state machine. Compared with the existing wireless sensor networks, simulation results show that the proposed security localization technology method can resist many kinds of attacks with low communication and time consumption.